MANAJEMEN KLUB BULU TANGKIS KOTA PONTIANAK DAN KUBU RAYA - Umam Fraziar Putra Narendra; Y. Touvan J; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe problem in this study is that there are differences in the performance results of each badminton club in the city of Pontianak and kubu raya, seen from the intensity of the training, the variation of training, and the time (days) of training each club is almost the same. But the difference is the results of the matches in each category of games that win an average is the same club. This research is quantitative descriptive. The method used in this study is a survey method with data collection techniques using a questionnaire test. The population in this study amounted to 6 clubs, the clubs studied were badminton clubs in the city of Pontianak and kubu raya that had SI PBSI with the source of the data being the administrators, coaches, and athletes in the club. The data analysis technique used quantitative descriptive analysis which was made in a descriptive form. Based on the results of data analysis on the planning management function that is categorized sufficiently with a percentage of 54.67%, the results of the management function of organizing the category are good with a percentage of 64.25%, the results of the directional management function research category are good with a percentage of 79.01%, and the results of the research function supervisory management is in the moderate category with a percentage of 43.65%.Keywords: Management, Badminton Club